Copper carbon composite wire with a uniform carbon dispersion made by friction extrusion. (May 2021) - Li, Xiao; Zhou, Chen; Overman, Nicole; Ma, Xiaolong; Canfield, Nathan; Kappagantula, Keerti; Schroth, James; Grant, Glenn
Graphical abstract: Highlights: Manufactured bulk size copper carbon composite wire from mixed powder using friction extrusion process. Achieved highly uniform sub-micron level carbon dispersion via severe shear deformation. Discussed the mechanism of mixing and dispersion in friction extrusion process. Improved specific heat capacity of the copper carbon wire 30 % compared to pure copper while the density was reduced by 29 %. Abstract: Copper-carbon composites are a group of materials with excellent mechanical, electrical, thermal, and tribological properties. However, bulk size copper-carbon composites made by the traditional manufacturing processes, like rolling or extrusion, fall short of reaching some of these properties predicted by theory or demonstrated only by samples at centimeter scale or smaller. The two main challenges to the successful scaling-up are: 1) to uniformly disperse carbon in the metal matrix; 2) to avoid degradation due to oxidation or reaction from overheating. In this work, we first demonstrate friction extrusion as a new method to make bulk-size void-free copper-carbon composite wires with homogenized carbon dispersion. Three different carbon varieties, graphite powder, graphene nanopowder, and carbon nanotubes, were added to the copper matrix with the concentration ranging from 0.5 wt% to 15 wt%. Special tooling, processing parameters, and procedures were developed, especially for high carbon content samples. Ten-fold reductions of both copper grain size and carbon particle size were achieved and attributed to the high shear deformation. Energy dispersive X-ray spectrometry indicates the carbon powder was refined to a sub-micron level and uniformly dispersed in the copper matrix. Compared with that of pure copper, the thermal capacity of the composite wire increases by 30 % while density reduces by 29 %.